Du merveilleux et du fantastique au surnaturel chrétien : le parcours initiatique du héros dans le Roman en prose de Perceval - Claude Lachet (Revue des Langues Romanes)
This study, based on Francis Dubost’s thesis, Aspects fantastiques de la littérature narrative médiévale (xiie-xiiie siècles), L’Autre, l’Ailleurs, l’Autrefois, traces Perceval’s initiatory itinerary: The “fantastic encounters” he has with the three couples of Beau Mauvais and Rosette, Urbain and his lady, the Black Knight and the fairy, help him to understand that he must give up his stay in the castle of the magic chessboard and with his “Queen”, and distance himself from feminine attractions and amorous bewitchments if he is to succeed in his quest. The final part traces the various stages of his spiritual elevation : his forgetfulness of God, his confession to his hermit uncle, his return to the Fisher King, the miraculous healing of Bron, the lordship of the Grail and sainthood.